Molecular and structural basis of ESCRT-III recruitment to membranes during archaeal cell division - Samson, R; Obita, T; Hodgson, B; Shaw, M; Chong, P; Williams, R; Bell, S (Elsevier, 2011)
Members of the crenarchaeal kingdom, such as Sulfolobus, divide by binary fission yet lack genes for the otherwise near-ubiquitous tubulin and actin superfamilies of cytoskeletal proteins. Recent work has established that Sulfolobus homologs of the eukaryotic ESCRT-III and Vps4 components of the ESCRT machinery play an important role in Sulfolobus cell division. In eukaryotes, several pathways recruit ESCRT-III proteins to their sites of action. However, the positioning determinants for archaeal ESCRT-III are not known. Here, we identify a protein, CdvA, that is responsible for recruiting Sulfolobus ESCRT-III to membranes. Overexpression of the isolated ESCRT-III domain that interacts with CdvA results in the generation of nucleoid-free cells. Furthermore, CdvA and ESCRT-III synergize to deform archaeal membranes in vitro. The structure of the CdvA/ESCRT-III interface gives insight into the evolution of the more complex and modular eukaryotic ESCRT complex.